Report of a Committee of the Dublin Statistical Society on the registration of marriages, births, and deaths in Ireland, presented to the Society by the Council - Dublin Statistical Society. Special Committee on Registration of Marriages, Births and Deaths (Dublin Statistical Society, 1859)
Marriages, births and deaths are now registered not only in England and Scotland, but (with the single exception of Ireland) in all the civilized states of Europe, whether Roman Catholic or Protestant; and we beg to report that we consider the subject to be one of extreme importance, and that a uniform Registration of Marriages, Births and Deaths is required as an essential condition for many sanitary reforms affecting the welfare of the population, and as an additional protection to the moral and material interests of society.
Presented: 28th October, 1858
Keywords: Registration of Marriages, Births and Deaths; 314.15